ERK1/2 mediates the lipopolysaccharide-induced upregulation of FGF-2, uPA, MMP-2, MMP-9 and cellular migration in cardiac fibroblasts. (1st June 2019) - Chen, Liang-Chi; Shibu, Marthandam Asokan; Liu, Chung-Jung; Han, Chien-Kuo; Ju, Da-Tong; Chen, Pei-Yu; Viswanadha, Vijaya Padma; Lai, Chao-Hung; Kuo, Wei-Wen; Huang, Chih-Yang
Abstract: Myocardial fibrosis is a critical event during septic shock. Upregulation in the fibrosis signaling cascade proteins such as fibroblast growth factor (FGF), urokinase plasminogen activator (uPA), tissue plasminogen activator (tPA) and activation of matrix metalloproteinases (MMPs) are widely associated with the development of myocardial infarction, dilated cardiomyopathy, cardiac fibrosis and heart failure. However, evidences suggest that the common upstream mediators of fibrosis cascade play little role in cardiac fibrosis induced by LPS; further, it is unknown if LPS directly triggers the expressions and/or activity of FGF-2, uPA, tPA, MMP-2 and MMP-9 in cardiac fibroblasts. In the present study, we treated primary cultures of cardiac fibroblasts with LPS to explore whether LPS upregulates FGF-2, uPA, tPA, MMP-2, MMP-9 and enhance cellular migration. Further the precise molecular and cellular mechanisms behind these LPS induced responses were identified. Inhibition assays on MAPKs using U0126 (ERK1/2 inhibitor), SB203580 (p38 MAPK inhibitor), SP600125 (JNK1/2 inhibitor), CsA (calcineurin inhibitor) and QNZ (NFκB inhibitor) show that LPS-induced upregulation of FGF-2, uPA, MMP-2 and MMP-9 in cardiac fibroblasts was mediated through ERK1/2 signaling. Collectively, our results provide a link between LPS-induced cardiac dysfunction and ERK1/2 signaling pathway and thereby implies ERK1/2 as a possible target to regulate LPS induced upregulation of FGF-2, uPA, MMP-2, MMP-9 and cellular migration in cardiac fibroblasts. Highlights: LPS triggers proinflammatory cytokines that affects heart. LPS induced cardiac dysfunction is associated with cardiac dilation and fibrosis. Cardiac effects of LPS includes activation of FGF-2, uPA, tPA, MMP-2 and MMP. The LPS mediated fibrotic events are mediated by ERK1/2 in cardiac fibroblasts.